Pengelolaan Dana Desa Sebagai Upaya Pemberdayaan Masyarakat dan Peningkatan Pembangunan - Retno Wahyuni (Universitas Islam Kadiri, 2020)
Village Funds in the sample villages was still focused on the village development program (infrastructure development) and only a small portion of the Village Fund was utilized for community empowerment. The use of Village Funds raises a classic problem in the use of the Village Fund system in that the designation does not produce results that are suitable for village development. The study of Village Fund management is very interesting because each village has different uniqueness and characteristics. The purpose of this study is to find the pattern of the Village Fund management process in Panggungrejo District, Blitar Regency, a barrier and driver of Village Fund management in Panggungrejo District, Blitar Regency and prove the role of the Village Fund in community empowerment and increased development in Panggungrejo District, Blitar Regency. The primary data sources in this study are the Village Head, Village Secretary, Village Treasurer, Activity Implementation Team (TPK), Village Assistant and Community. In this study data collection techniques using triangulation / combined techniques namely observation, interviews and documentation. The results showed that (1) Village fund management in the District of Panggungrejo has been carried out well starting from planning, budgeting, implementation, administration, reporting and accountability in accordance with the provisions; (2) Obstacles in the management of Village Funds are the dominance of the Village Head in village financial management, poor quality RAB, very small allocation of funds for community empowerment activities, disbursement of funds disbursement with the proposed SPP, financial reporting and accountability are not timely. While the driver of the management of the Village Fund is the motivation of the community to advance the region, a large workforce, supporting PKT, HR Village staff capable of managing the Village Fund. Village Funds in Panggungrejo Subdistrict Most of it is allocated for physical development: road rebates, construction of village bridges, construction of sewers, TPT, construction and maintenance of madin / TK buildings, organization of Posyandu and procurement of village website networks. Community Empowerment in Panggungrejo District has a very small budget allocation of only around 3% of the total Village Fund budget. The small budget makes the impact of empowerment activities less felt by the community.